Transmedial presence of verbal texts in architecture and public space. Between informativity and emotivity - Elżbieta Chrzanowska-Kluczewska (Когниция, коммуникация, дискурс)
From the semiotic viewpoint, architectonic structures and the surrounding public spaces can be seen as texts to be read and interpreted within proper historical, social, and cultural contexts. In addition, they are almost always multimodal, that is polysemiotic texts whose content becomes complemented with pictorial elements (paintings, sculptures), with written or oral language and, on occasion, with music.